Investigation of the psychometric properties of the Turkish child-friendly Oral Health Questionnaire - Gonca Karayağiz Muslu; Gülay Manav; Özgül Carti Dörterler; Recep Kara (BMC, 2024)
Abstract Background Oral problems are a common occurrence among school-age children. In order to develop effective oral health interventions and services, it is essential to determine children's oral health behaviours using an internationally accepted standardised instrument that is child-friendly. However, no instrument currently exists to measure oral health according to the Theory of Planned Behaviour (TPB) in Turkish school-aged children. The aim of this study was to investigate the psychometric properties of the Oral Health Questionnaire, which includes the components of the theory of planned behavior such as attitude toward children's oral health, subjective norm, perceived behavioral control, and self-efficacy, for the Turkish population. Methods This was a methodological-descriptive-correlational study conducted on 298 school children aged 9-10 years. Data were collected using The Oral Health Questionnaire. The data were evaluated using explanatory and confirmatory factor analysis, Cronbach's alpha, item-total score correlation, and Pearson product-moment correlation analysis. Results Factor analysis confirmed the five-dimensional structure. The factor loads were greater than 0.30, and all fit indices were greater than 0.90. The model consistency indexes were found to be X2 = 146.95, RMSEA = 0.053, GFI = 0.94, CFI = 0.98, IFI = 0.97, and NNFI = 0.97. The Cronbach's alpha values of its sub-dimensions were 0.71 and 0.80. Conclusions The Turkish version of Oral Health Questionnaire is considered a reliable and valid instrument that can be used by professionals to determine children's attitudes, subjective norms, perceived behavioral control, and oral and dental health intentions toward tooth brushing.